PARENTAL TREATMENT STYLES AS PERCEIVED BY ADOLESCENTS AND THEIR RELATIONSHIP TO PSYCHOLOGICAL SECURITY AMONG SECONDARY SCHOOL STUDENTS IN TAMANRASSET - Hafida Houhou,; Khadidja Mositfa,; Zakaria Horma, (International Journal of Innovative Technologies in Social Science, 2025)
This study aimed to investigate the relationship between parental treatment styles—as perceived by adolescents—and psychological security among secondary school students in Tamanrasset. A descriptive-correlational research design was employed, with a randomly selected sample of 40 male and female students. The researchers utilized two validated instruments: the Parental Treatment Styles Scale (Yaghshi, 2015) and the Psychological Security Scale (Shaqir, 2005). Data were analyzed using SPSS software. The findings revealed: (1) a weak but statistically significant correlation between perceived parental treatment styles and psychological security; (2) a moderate level of psychological security among the participants; and (3) no statistically significant gender differences in adolescents’ perceptions of parental treatment styles. The results were discussed in light of prior literature and the socio-cultural context of the studied sample.